2010
DOI: 10.1016/j.jcmg.2010.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Stress Myocardial Contrast Echocardiography for the Detection of Coronary Artery Disease

Abstract: Adenosine MCE achieved favorable diagnostic performance in identifying the presence and functional significance of coronary stenosis. Adenosine MCE may be useful in the clinical setting for evaluating patients with suspected CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 35 publications
0
21
0
2
Order By: Relevance
“…1,2 Real-time myocardial contrast echocardiography (RTMCE), using a continuous infusion of ultrasound contrast, has been shown to be effective for detection of myocardial perfusion abnormalities during either vasodilator or demand stress. [3][4][5][6][7][8][9][10][11][12][13] Although RTMCE has been used to detect coronary artery stenoses (CAD) with vasodilators such as dipyridamole and adenosine, 10 -13 its use with a direct A2A agonist bolus offers the potential to detect CAD within minutes at the bedside without the need for exposure to ionizing radiation or cumbersome infusion setups. 14,15 The purpose of the present study was to determine the sensitivity, specificity, and accuracy of RTMCE in the detection of CAD after a regadenoson bolus injection.…”
mentioning
confidence: 99%
“…1,2 Real-time myocardial contrast echocardiography (RTMCE), using a continuous infusion of ultrasound contrast, has been shown to be effective for detection of myocardial perfusion abnormalities during either vasodilator or demand stress. [3][4][5][6][7][8][9][10][11][12][13] Although RTMCE has been used to detect coronary artery stenoses (CAD) with vasodilators such as dipyridamole and adenosine, 10 -13 its use with a direct A2A agonist bolus offers the potential to detect CAD within minutes at the bedside without the need for exposure to ionizing radiation or cumbersome infusion setups. 14,15 The purpose of the present study was to determine the sensitivity, specificity, and accuracy of RTMCE in the detection of CAD after a regadenoson bolus injection.…”
mentioning
confidence: 99%
“…However in a recent study about interobserver variability of stress induced first-pass MR has showed only moderate agreement which has been influenced by experience and systematic reading criteria [16]. Reversible adenosine induced perfusion defects obtained from cardiac MR has found ificity, and accuracy of this modality compared to X-ray angiography and cardiac MR were 85%, 76% and 82% versus 85%, 74% and 79% respectively [25]. Although it has been documented that interobserver agreement is better in the contrast enhanced echocardiography however we employed a non-contrast protocol in our study [26].…”
Section: Discussionmentioning
confidence: 99%
“…16,17 It may also occur with severe CAD. 18 Although only 1% of the patients underwent Figure 4 Incremental predictive values (depicted on the y axis as c 2 values) of resting LV function, WM assessment, and MP assessment over clinical variables, using sequential Cox regression models.…”
Section: Discussionmentioning
confidence: 99%